PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. NIAGA REDJA ABADI KOTA TASIKMALAYA (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the simultaneous and partial effect of Competence and Work Discipline on Employee Performance at PT. Commerce Redja Abadi Tasikmalaya City. The research method used in this study is a quantitative method with an associative (causality) and census analysis approach. The population in this study amounted to 50 employees of PT. Commerce Redja Abadi Tasikmalaya City. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results of this study indicate that competence and work discipline simultaneously have a significant effect on employee performance at PT. Commerce Redja Abadi Tasikmalaya City. Competence partially has a significant effect on Employee Performance at PT. Niaga Redja Abadi Tasikmalaya City and Work Discipline partially have a significant effect on Employee Performance at PT. Commerce Redja Abadi Tasikmalaya City.